Selecting sterilization conditions for the explants of different potato varieties to be in vitro introduced into the culture - Amantayev, N.G.; Silantyeva, M.M.; Khassanov, V.T. («Академик Е.А. Бөкетов атындағы Қарағанды университеті» КЕАҚ баспасы, 2023)
An explant is a fragment o f plant tissue or organ that is incubated on its own or used to produce a primary callus. The introduction o f any plant’s tissues into the culture in vitro begins with the selection o f an uninfected viable explant. The authors presented the results o f the effect o f various sterilizing agents as well as the treatment timing on the viability o f plant explants during microclonal propagation o f potatoes o f the following varieties: Aladin, Gala, Nevsky, Udacha and Kostanay Novosti. The meristem sprouts from potato tubers were used as parent material. The following commercial sterilizing agents were used: Bleach (Belizna), Tween 20, Lyzoformin 3000, 96 % ethyl alcohol. The influence of sterilizing agents as well as the timing of the treatment on the viability of explants and their contamination is analyzed. As a result o f the experiments, it has been found that the most effective sterilizing agent is the 3 % bleach and 96 % ethyl alcohol with exposure duration o f 10 minutes. Based on the results o f the experiment, it is proposed to use the 3 % bleach with an exposure time o f 10 minutes as the main sterilizing agent, and the 96 % ethyl alcohol as some pretreatment o f explants to reduce surface contamination. The authors believe that the 96 % ethyl alcohol is the best option for sterilizing solutions since it is a non-toxic, gentle method o f sterilization with minimum damage of the plant material tissues.
Әртүрлі картоп сорттарының экспланттарын in vitro жағдайында дақылға енгізу мақсатында оларды зарарсыздандыру жолын таңдау
Подбор условий стерилизации эксплантов различных сортов картофеля для введения в культуру in vitro
Keywords: potato tubers; meristem sprouts; sterilizing solutions; explant; exposure; sterilization